Community development, bricolage, and celebrity-driven activism: A case study of Half the Sky movement. Issue 4 (8th August 2022) - Casey, Sarah; Holliday, Penny; Weber, Ian
ABSTRACT: Celebrity journalists Nicholas Kristof and Sheryl WuDunn launched Half the Sky, a book exploring the feasibility of mass-awareness and community-based campaigning platforms. The book, which created a grassroots feminist movement for women in the Global South, had broad cultural effects, with the publisher launching a 25 th hardcopy print run within a year of its 2009 release. The Half the Sky movement lasted over a decade, maintaining momentum via the recruitment of public figures like Oprah Winfrey, Bill Clinton, and the Gates Family. While recognizing its methods and premises are not without issues, we focus on how activists and campaigners employed entrepreneurial, network and collaborative-social bricolage tactics and strategies regardless of the campaign targets. We utilize an extended case study of the book, movement, and celebrity-led activism to support the analysis of these tactics and strategies and to propose a more sustainable approach for community-based social change.